On the application of thermodynamic methods to the analysis of quantum states - Arkhipov, V.V.; Kolt, M.V. (Publishing House of the KarSU named after E.A.Buketov, 2011)
The presented work is devoted to the problem of stability of quantum systems. There are investigated possibilities of the statistical entropy using as a criteria for the equilibrium. The harmonic oscillator is used as an example for classical and quantum theories. It’s shown that from thermodynamics point of view the quantum distributions are more advantageous than classical ones.
Keywords: stability; quantum systems; statistical entropy; criteria for the equilibrium; quantum distributions